A Mobile Detector for Muon Measurements Based on Two Different Techniques. (23rd April 2013) - Mitrica, B.; Stanca, D.; Petcu, M.; Brancus, I. M.; Margineanu, R.; Apostu, A.; Gomoiu, C.; Saftoiu, A.; Toma, G.; Rebel, H.; Haungs, A.; Sima, O.; et al.
Abstract : Precise measurements of the muon flux are important for different practical applications, both in environmental studies and for the estimation of the water equivalent depths of underground sites. A mobile detector for cosmic muon flux measurements has been set up at IFIN-HH, Romania. The device is used to measure the muon flux on different locations at the surface and underground. Its first configuration, not used in the present, has been composed of two 1 m 2 scintillator plates, each viewed by wave length shifters and read out by two Photomultiplier Tubes (PMTs). A more recent configuration, consists of two 1 m 2 detection layers, each one including four 1 · 0, 25 m 2 large scintillator plates. The light output in each plate is collected by twelve optical fibers and then read out by one PMT. Comparative results were obtained with both configurations.